Pengaruh Kompensasi, Motivasi Terhadap Kinerja Pegawai Melalui Variabel Intervening Kepuasan Kerja Dan Perspektif Maqashid Syariah Pada RSUD Dr. Pirngadi Kota Medan - Nurhidayanti, Nurhidayanti; Tarigan, Azhari Akmal; Nasution, Syukri Albani (Jurnal Ilmiah Ekonomi Islam, 2022)
Performance or performance is a description of the level of achievement of the implementation of a program of activities or policies in realizing the goals, objectives, vision and mission of the organization as outlined through the strategic planning of an organization. Employee performance is the result of work in quality and quantity achieved by an employee in carrying out his duties in accordance with with the responsibilities assigned to him. The purpose of this study was to determine the direct and indirect effects of compensation, motivation, job satisfaction on performance at RSUD Dr. Pirngadi Medan City. This research method uses a quantitative approach with path analysis and uses the SPSS version 20.0 program. This study uses a questionnaire with a sample of 100 respondents. The results of this study indicate that the compensation variable, motivation, on job satisfaction through performance is 54.5% and the remaining 45.5% is influenced by other variables. While the compensation variable, motivation on job satisfaction is 55.7% and the remaining 44.3% is influenced by other variables. intervention at RSUD Dr. Pirngadi Medan City with 95% confidence level and 5% error rate. Maqashid al-shari'ah can be interpreted as God's goal as shari' in establishing an integrated law for his servants. The essence of maqashid al-syari'ah is to realize goodness while avoiding evil or attracting benefits (maslahah).